Conversor CC-CC Push-Pull trifásico bidirecional - Trigueiro, Hélio Oliveira (2018)
With the continuous growth in microgeneration processes, studies of electric vehicles and systems that require the process of conversion of the electric voltage, studies of the various elements that compose those systems are necessary. One of them is the DC-DC converter, which will adapt the voltage from a generator system to a value that may be higher or lower than the original, depending on the designed system. Thus, in this work, the study of a DC-DC converter with bidirectionality will be presented, being able to operate with two directions of power flow: from the low voltage side to the high voltage side and vice versa. The topology of the converter chosen was the three-phase push-pull, with the control made by PI controllers and PWM modulation. Simulation results validate the proposed system, also an experimental study is shown.